Empire Mutual Life Insurance Company of New York; James Wight & Co, Carridge Stock; McGinnis & McGowan, Furniture; Lewis Jones & Son, Undertakers - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of Empire Mutual Life Insurance Company of New York; James Wight & Co, Carridge Stock; McGinnis & McGowan, Furniture; Lewis Jones & Son, Undertakers from the 1870 Boston City Directory